Effect of functional endoscopic sinus surgery on asthma control with nasal polyposis and chronic rhinosinusitis - Akdeniz, Önder; Dülger, Seyhan; Yılmaz Durmaz, Dilber; Şengören Dikiş, Özlem; Yıldız, Tekin (The European Research Journal, 2018)
Objective. The purpose of this study is to examine the effect of endoscopic sinus surgeons on the control of disease in asthma combined with chronic rhinosinusitis. Methods. Twenty-three asthma patients with chronic rhinosinusitis were evaluated retrospectively. They were assessed with asthma control test and pulmonary function tests. Subjective nasal obstruction assessment was done according to the nasal obstruction symptoms evaluation (NOSE) scale. Other subjective sinonasal complaints were classified using visual analogue scale (VAS). At postoperative third month, pulmonary function tests, asthma control test, NOSE and VAS were reevaluated.Results. According to asthma control test, number of patients under control, partial controlled and uncontrolled were 2/6/15 preoperatively and 14/4/5 postoperatively, respectively. There was permanent or partial improvoment in fullness in the nose sniffle of 95.7% according to NOSE. The most remarkable permanent improvement in the symptoms were seen in the feeling of pressure in the face of 75%, smell disorders of 66.7% according to sinonasal visual analogue scale assessment. NOSE and VAS values were significantly improved postoperatively (p < 0.05).Conclusions. Uncontrolled asthma associated with chronic rinosinusitis can benefit from functional endoscopic sinus surgery in asthma control level, nasal blockage symptoms and other sinonasal complaints.